Effects of bottom roughness on wave transmission across a submerged reef - Dinh, Quang Cuong; Nguyen, Quang Tao; Ho, Duc Dat; Mai, Cao Tri (Frontiers in Marine Science, 2023)
This paper presents a laboratory study to investigate the effects of bottom roughness on wave transmission across a submerged coral reef that has a steep fore-reef slope. Experimented models were carried out in wave flumes for four different bed roughness levels: including a smooth bed and three roughness heights. Our investigations showed that there is a significant dissipation of energy in short-period waves (SS-waves), owing to bottom friction, compared with that of infra-gravity waves (IG-waves). In addition, the study found that the IG-wave heights are increased slightly as waves propagate shoreward from the reef-edge surfzone, indicating that a significant portion of energy was transferred from SS-waves to IG-waves. Empirical formulae of wave energy dissipation due to bottom friction and non-linear transfer of energy among the SS- and IG-waves have been derived; these allow for the straightforward determination of wave heights and wave periods on the submerged reef. These local wave parameters can be used to design offshore structures on submerged coral reefs.